Dr Donald H. Colless, in Memoriam - Theischinger, Gunther (Zootaxa, 2013)
The life, work and success of Dr Donald H. Colless are treated in the preceding articles by people close to him and competent to do it. My desire is to briefly describe how this most successful scientist, one of the most remarkable people I have met, treated, inspired, encouraged and motivated an immigrant amateur entomologist who had just arrived in Australia. I was interested in continuing my taxonomic work on the Australian Tipulidae (Diptera) and various aquatic insect taxa, expanding from my previous studies on the European fauna.